Ecological validity, embodiment, and killjoy explanations in developmental psychology. (13th December 2017) - Zappettini, Shane
Abstract: Keven & Akins (K&A) present a compelling alternative to the case for neonatal orofacial imitation, offered by Meltzoff and Moore. However, they provide little concerning what lessons their proposal has to offer developmental psychology more generally. I suggest three candidates and elaborate on how they raise outstanding methodological and philosophical questions for the approach taken in the target article.